2005
DOI: 10.1016/j.jacc.2005.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Steps Toward the Percutaneous Replacement of Atrioventricular Valves

Abstract: Implantation of a semi-lunar valve in the tricuspid position is possible in ewes through a transcatheter approach. A disk-based nitinol stent is needed to allow valve implantation in the atrioventricular position. These studies open new perspectives into tricuspid as well as mitral valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(41 citation statements)
references
References 9 publications
0
37
0
4
Order By: Relevance
“…5,7,11,12 The present study offers mechanistic insights that can potentially be applied to improve repair for functional TR in both operative and newly emerging percutaneous approaches. 37 In the present study, we demonstrated that changes in the 3D annular shape also predicted functional TR, not just annular area alone, and hence, achievement of a saddle shape may be an important therapeutic goal beyond that of annular reduction alone. Ideally, annular remodeling with tricuspid annuloplasty should take into account the geometric changes that occur with TR, namely, increased circularity and planarity, and restore the normal bimodal-elliptical shape of the tricuspid annulus to reduce leaflet tethering and leaflet stress.…”
Section: Ton-nu Et Al Geometric Determinants Of Functional Tr 147mentioning
confidence: 50%
“…5,7,11,12 The present study offers mechanistic insights that can potentially be applied to improve repair for functional TR in both operative and newly emerging percutaneous approaches. 37 In the present study, we demonstrated that changes in the 3D annular shape also predicted functional TR, not just annular area alone, and hence, achievement of a saddle shape may be an important therapeutic goal beyond that of annular reduction alone. Ideally, annular remodeling with tricuspid annuloplasty should take into account the geometric changes that occur with TR, namely, increased circularity and planarity, and restore the normal bimodal-elliptical shape of the tricuspid annulus to reduce leaflet tethering and leaflet stress.…”
Section: Ton-nu Et Al Geometric Determinants Of Functional Tr 147mentioning
confidence: 50%
“…In 2005, Boudjemline et al 45 described a novel percutaneous tricuspid valve consisting of a bovine jugular venous valve mounted to a self-expanding nitinol frame consisting of 2 disks. The device was deployed through an 18F sheath in the right internal jugular vein, with right ventricular and right atrial disks deployed sequentially to sandwich the native tricuspid valve ( Figure 6).…”
Section: Relevance In the Percutaneous Eramentioning
confidence: 99%
“…As demonstrated by Boudjemline et al, 2 orthotopic valve replacement is possible but carries a risk of injury and paravalvular leakage. The vicinity to the endocardium is likely to contribute to ventricular arrhythmia.…”
Section: To the Editormentioning
confidence: 96%